A Study on Chemical and Bacteriological Analysis of Bore Water from Some Communities in Tirupathi Rural Areas of Chittoor District Andhra Pradesh India - Ernest David, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
A Study on Chemical and Bacteriological Analysis of Bore Water from Some Communities in Tirupathi Rural Areas of Chittoor District Andhra Pradesh India